Modified ρ-Bernstein Operators for Functions of Two Variables. (4th July 2021) - Agrawal, P. N.; Kajla, Arun; Kumar, Dharmendra
Abstract: In this manuscript, we consider a bivariate extension of modified ρ-Bernstein operators and obtain Voronovskaya type and Grüss Voronovskaya type theorems for these operators. Further, we determine the rate of convergence of these operators in terms of the complete and partial moduli of continuity and compute an estimate of the error in terms of the Peetre's K-functional. Also, we define the associated Generalized Boolean Sum (GBS) operators and study the rate of convergence of these operators with the aid of the mixed modulus of smoothness for the Bögel continuous and Bögel differentiable functions and the degree of approximation for the Lipschitz class of Bögel continuous functions.